98: Hanging, Choking and Near-Drowning in Children; Imaging Findings, Neurological Sequelae, and Outcomes. Issue 6 (1st June 2014) - Rossoni, M; Levin, S; Tay, KY; Prasad, AN
Abstract: BACKGROUND: Unintentional injury is the leading cause of death in youth ages one to 19, and suicide is the second leading cause of death in those ages 15 to 19. Asphyxiation injuries, including choking, drowning, and hanging, account for a great proportion of these injuries, with the latter two accounting for up to 18% of all suicides. There are few reports on the imaging and neurologic consequences of such injuries in contrast to extensive research on hypoxic insults in the perinatal period. OBJECTIVES: We report on the presentation, imaging findings, and sequelae of asphyxiation injuries outside the perinatal period. DESIGN/METHODS: A retrospective chart review was conducted of nine paediatric patients referred to a tertiary paediatric care hospital between 1990 and 2012. These children were all admitted to the Intensive Care Unit with severe asphyxiation injuries and were all assessed by a Paediatric Neurologist. The ages of the patients ranged from 14 months to 17 years, mean age of eight years. RESULTS: Asphyxiation resulted from aspiration (33% of cases), near-hanging (44% of cases), and near-drowning (11% of cases). In one case, the mechanism of injury was unclear, aspiration or near-drowning. All patients had evidence of hypoxic insult on neuroimaging. In the majority of patients, imaging demonstrated diffuse cortical and basal ganglia involvement, little white matter abnormality and minimal cerebral edema. 89% of the patients had an EEG performed. The background activity was abnormal, suggestive of diffuse and severe depression of cortical activity and graded IV–V on the dysrhythmia scale in 75% of the patients. Medical support was withdrawn within one week in 56% of patients and after four months in 11%, with 22% of patients going on to cadaveric donation. Forty-four percent of patients survived to one year post-injury, 100% of which developed severe spasticity and feeding problems. Therefore, at one year the mortality rate was 67% with severe morbidity in 100% of survivors. CONCLUSIONS: We describe nine children with severe acute hypoxic insult. The majority of patients exhibited severe neurological dysfunction on EEG. All patients had significant abnormalities on neuroimaging. Brain MRIs of these patients showed a unique pattern of cortical and basal ganglia involvement, which has not been previously described in the literature. The outcomes from these injuries can be devastating, with significant morbidity and mortality. Injury prevention strategies and resuscitation skills should be included in publically funded programs for parents and caregivers of children.